2018
DOI: 10.1007/s10899-018-09815-y
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Treatments for Disordered Gambling: A Meta-analysis

Abstract: Disordered gambling is a public health concern associated with detrimental consequences for affected individuals and social costs. Currently, opioid antagonists are considered the first-line treatments to reduce symptoms of uncontrolled gambling. Only recently, glutamatergic agents and combined pharmacological and psychological treatments have been examined appearing promising options for the management of gambling disorder. A multilevel literature search yielded 34 studies including open-label and placebo-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
35
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 106 publications
(97 reference statements)
6
35
0
1
Order By: Relevance
“…A similar, but nonsignificant result was also observed for the reduction of the global severity of SA. These findings are consistent with those from Asian IA research (Chun et al, 2017), and with those gained from disordered gambling (Goslar et al, 2017;Leibetseder et al, 2011;Pallesen et al, 2005), suggesting that the manifestation of addictive behaviors requires more intensive treatment to achieve improvement.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…A similar, but nonsignificant result was also observed for the reduction of the global severity of SA. These findings are consistent with those from Asian IA research (Chun et al, 2017), and with those gained from disordered gambling (Goslar et al, 2017;Leibetseder et al, 2011;Pallesen et al, 2005), suggesting that the manifestation of addictive behaviors requires more intensive treatment to achieve improvement.…”
Section: Discussionsupporting
confidence: 86%
“…Although most information was provided by IA treatment outcome studies, and data from controlled trials is still limited, psychological and pharmacological approaches showed favorable short-term effects across the three conditions, which are comparable to those applied for substance use and disordered gambling (e.g., Goslar et al, 2017;Grant et al, 2010) supporting our hypotheses. These findings are not sufficient for clarifying the classification of IA, SA and CB within the spectrum of psychiatric disorders due to missing validation of diagnostic criteria, and limited epidemiological, genetic and neurobiological data (e.g., Grant et al, 2010).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…On the other hand, given the lack of efficient and specific anti‐ICD drugs (Mestre et al., 2013), understanding the etiology and mechanisms of ICDs empowers the development of novel pharmacotherapies of these disorders. For example, psychostimulants (e.g., alpha‐2 agonists) and atomoxetine treat disruptive and aggressive behaviors (Pringsheim, Hirsch, Gardner, & Gorman, 2015), whereas compulsive gambling is treated with a glutamatergic agent topiramate combined with lithium (Goslar, Leibetseder, Muench, Hofmann, & Laireiter, 2019; Wittekind et al., 2019). At the same time, a correct ICD diagnosis becomes essential for selecting their optimal therapy.…”
Section: Discussionmentioning
confidence: 99%